Kajian Teknis Penggalian Lapisan Tanah Atas dan Kaksa untuk Meningkatkan Laju Pemindahan Tanah pada Kapal Keruk 21 Singkep 1 di Perairan Air Kantung, Sungailiat, Bangka: Technical Study of Top Soil and Kaksa Diggingto Improve Soil Removal Rate of Dredger 21 Singkep 1 on Air Kantung Waters, Sungailiat, Bangka Regency - Saputra, Aleo; Tono, E.P.S.B Taman; Guskarnali, Guskarnali (Program Studi Teknik Pertambangan Universitas Bangka Belitung, 2017)
One of the parameters of dredgers succeed is the rate success of overburden and kaksa per hour. For Dredger 21 Singkep 1 in September 2016 its LPT reach 493 m3/h, so it is still not yet achieved the ideal LPT dredger with bowl measuring 24 cuft of 782,44 m3/hour. The technical study on the excavation of top soil and kaksa done through the stages of research that consists of data collection, grouping the data as well as data processing and analysis. The results of this study indicateLPT ideal on the excavation of top soil for 978,05 m3/hour can be achieved by setting an average depth of 0.54 m emphasis ladder on the side wire speed of 6.82 m/minute and the pull wire speed setting aside that is equal to 8,04 m/minute at an average depth of 0.46 m emphasis ladder, while ideal in the excavation layer kaksa’s LPT of 586.83 m3/hour can be achieved by setting an average depth of 0.26 m emphasis ladder on the side of the wire speed 8.73 m/minute and the pull wire speed setting aside of 11.16 m/ minute at an average depth of 0.20 m emphasis ladder. LPT excavation of topsoil using face long methods reaches 845.38 m3/hour, or an increase of 19.7% from the LPT on short face methods that is equal to 652.78 m3/hour.